Dwie drogi, dwa ruchy i zdrada – Ukraińskie narracje o rewolucji na granicie i ludowym ruchu Ukrainy - Jędraszczyk , Katarzyna (Studia Europaea Gnesnensia, 2019)
The article analyzes the Ukrainian narrative concerning the role of student protests in Ukraine in October 1990. The narrative in question competes with much more widespread knowledge about the actions undertaken by the so-called Rukh (People’s Movement of Ukraine, Narodnyi Rukh Ukrajiny) and its leaders as the nation strove for independence. The memory of the so-called the Revolution on Granite is passed on by the participants of those events. Thanks to the inclusive narrative, also moderated by the state, the alternative repre-sentation of the past and historiography has no potential to provoke a conflict of memory, being merely a different interpretative approach indulging in hypothetical scenarios of development of Ukrainian democracy had the key demands of the protesters been met (early elections in 1991).